Kemampuan Siswa Kelas VIII dalam Menulis Puisi di SMP Negeri 35 Kecamatan Bukit Raya Kota Pekanbaru Tahun Ajaran 2022/2023 - Tunisa, Avini; Tinambunan, Jamilin (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Poetry is a form of literary work that is presented in beautiful and imaginative language and can be studied from various aspects. The problem studied in this study is how the ability of class VIII students to write poetry at SMP Negeri 35, Bukit Raya sub-district, Pekanbaru city for the 2022/2023 academic year based on the physical structure of poetry and the inner structure of poetry. The purpose of this study is to describe, analyze, interpret and conclude data on students' ability to write poetry based on physical structure and mental structure, This study using many methods about writing and choice about second sections it can be concluded that the average ability of Grade VIII students to write poetry at SMP Negeri 35, Bukit Raya District, Pekanbaru City for the 2022/2023 school year, in terms of physical structure = 67.7 in the poor category and the ability of class VIII students to write poetry at SMP Negeri 35, Bukit Raya sub-district, Pekanbaru, for the 2022/2023 academic year, in terms of mental structure = 81.6, in the good category. So the overall result of the ability of class VIII students in writing poetry at SMP Negeri 35, Bukit Raya sub-district, Pekanbaru city, for the 2022/2023 academic year is 71.6 in the fairly good category.